2007
DOI: 10.1038/sj.ki.5002054
|View full text |Cite
|
Sign up to set email alerts
|

TNFA2 and d2 alleles of the tumor necrosis factor alpha gene polymorphism are associated with onset/occurrence of idiopathic membranous nephropathy

Abstract: Idiopathic membranous nephropathy (IMN) has a strong association with the major histocompatibility complex HLA B8DR3(17)DQ2 haplotype. The tumor necrosis factor (TNF)A gene is located within the major histocompatibility complex region on chromosome 6. We have studied the influence of two functional polymorphisms; the -308 (promoter region) and the TNFd microsatellites on initiation and/or progression of IMN. This was a case-control study comparing data from 100 Caucasians patients (67 male subjects; 67%) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 33 publications
(38 reference statements)
4
21
1
Order By: Relevance
“…19 TNF contributes to the initiation and progression of renal injury. 20,21 Although the À308G-A polymorph- Genetic variants and chronic kidney disease T Yoshida et al ism of TNF 22,23 was earlier found to be associated with CKD, the À850C-T polymorphism of TNF has not been related to this condition. The variant T allele of the À850C-T polymorphism of TNF was associated with an increased risk of Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…19 TNF contributes to the initiation and progression of renal injury. 20,21 Although the À308G-A polymorph- Genetic variants and chronic kidney disease T Yoshida et al ism of TNF 22,23 was earlier found to be associated with CKD, the À850C-T polymorphism of TNF has not been related to this condition. The variant T allele of the À850C-T polymorphism of TNF was associated with an increased risk of Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this association is the first found between genetic variants and clinical outcome in IMN. Thibaudin et al (40) reported an association study of TNF-a gene polymorphisms with IMN. This group found a significant association of a SNP in the promoter region and a downstream microsatellite of the TNF-a gene with IMN susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that cytokines generated in the airways in response to air pollution can spill over into the circulation, influencing autoimmune responses and distant events [89]. Air pollution increases the circulating levels of inflammation mediators, such as TNF-α, IL-6, and plasminogen activator inhibitor-1 [88, 90], and genetic polymorphisms in these cytokines are associated with the development of MN [91-95]. …”
Section: Environmental Studies Of Pmnmentioning
confidence: 99%